A Sensitive Fluorescence Biosensor for Silver Ions (Ag+) Detection Based on C-Ag+-C Structure and Exonuclease III-Assisted Dual-Recycling Amplification - Yubin Li; Jiaming Yuan; Zexi Xu (Journal of Analytical Methods in Chemistry)
A C-Ag+-C structure-based fluorescence biosensor with novel combination design of exonuclease III (Exo III) dual-recycling amplification is proposed for the application of silver ions (Ag+) detection. Since oligo-1 involves C-C mismatches, the presence of Ag+ can be captured to form C-Ag+-C base pairs, which results in a double-helix structure with a blunt terminus. The double-helix structure can be cleaved by EXO III to release short mononucleotide fragments (trigger DNA) and Ag+. Released Ag+ can form new bindings with oligo-1, and other trigger DNA can be produced in the digestion cycles. Hybridization with the signal DNA (oligo-2) transforms a trigger DNA into double-stranded DNA with blunt terminus which can be cleaved by Exo III to reproduce the trigger DNA and form guanine- (G-) quadruplex DNA. The trigger DNA returns free to the solution and hybridizes with another signal DNA, which realizes the dual-recycling amplification. The G-quadruplex DNA can be reported by N-methylmesoporphyrin IX (NMM), a specific G-quadruplex DNA fluorochrome. This method allows Ag+ to be determined in the 5 to 1500 pmol/L concentration range, with a 2 pmol/L detection limit, and it has been successfully applied to the detection of Ag+ in real samples.